Contemporary Synthesis of Ultrasmall (sub‐10 nm) Upconverting Nanomaterials. Issue 6 (12th June 2020) - Joshi, Tanmaya; Mamat, Constantin; Stephan, Holger
Abstract: Due to their unique photophysical properties, upconverting nanoparticles (UCNPs), i. e. particles capable of converting near‐infrared (NIR) photons into tunable emissions in the range of ultraviolet (UV) to NIR, have great potential for use in various biomedical fields such as bioimaging, photodynamic therapy and bioanalytical applications. As far as biomedical applications are concerned, these materials have a number of advantageous properties such as brilliant luminescence and exceptional photostability. Very small "stealth" particles (sub‐10 nm), which can circulate in the body largely undetected by the immune system, are particularly important for in vivo use. The fabrication of such particles, which simultaneously have a defined (ultrasmall) size and the required optical properties, is a great challenge and an area that is in its infancy. This minireview provides a concise overview of recent developments on appropriate synthetic methodologies to produce such UCNPs. Particular attention was given to the influence of both surfactants and dopants used to precisely adjust size, crystalline phase and optical properties of UCNPs. Abstract : Making small smaller : Both surfactant ratio and ion dopants can play a critical role in producing upconverting nanoparticles that are sub‐10 nm in size.